Whole Genome Sequence of Bacillus velezensis Strain GUMT319: A Potential Biocontrol Agent Against Tobacco Black Shank Disease - Ding, Haixia; Mo, Weidi; Yu, Shui; Cheng, Huanhuan; Peng, Lijuan; Liu, Zuoyi (Frontiers in Microbiology, 2021)
Phytophthora nicotianae causes black shank, a serious soil-borne disease, in tobacco. In this study, the Bacillus strain GUMT319 was isolated from the rhizosphere of healthy tobacco plants grown in a field in Guizhou with a high incidence of tobacco black shank. Genome sequencing revealed that GUMT319 contained a single circular chromosome 3,940,023 bp in length, with 4,053 predicted genes and an average GC content of 46.6%. Based on phylogenomic analyses, GUMT319 was designated as Bacillus velezensis. The genome of GUMT319 contained more than 60 genes and 13 gene clusters that have previously been found to be active in antifungal mechanisms, biofilm formation, and chemotaxis motility. Additionally, confocal laser scanning microscopy and scanning electron microscopy showed that GUMT319 formed a spatially organized biofilm in vivo. In addition, lauric acid negatively regulated biofilm formation. This is the first study to report that nicotine in tobacco root exudates was a chemoattractant for biocontrol Bacillus strains. In this study, we identified new interactions between beneficial microorganisms and tobacco roots in the rhizosphere. Moreover, dual-culture tests in vitro showed that GUMT319 inhibited the growth of P. nicotianae and also displayed inhibitory effects against eight other plant pathogens, including Colletotrichum scovillei, Colletotrichum capsici, Fusarium carminascens, Sclerotinia sclerotiorum, Alternaria alternata, Phomopsis sp., Phyllosticta sorghina, and Exserohilum turcicum. Furthermore, GUMT319 exhibited >70% control efficiency against tobacco black shank in field experiments conducted in 2018–2020. Thus, GUMT319 was more effective in controlling the incidence of tobacco black shank than other treatments including fungicide application. Overall, these results suggested that GUMT319 (B. velezensis) could be used as a potential biocontrol agent against tobacco black shank.